Enhanced Therapeutic Efficacy of iRGD-Conjugated Crosslinked Multilayer Liposomes for Drug Delivery. (15th April 2013) - Liu, Yarong; Ji, Man; Wong, Michael K.; Joo, Kye-Il; Wang, Pin
Abstract : Targeting nanoparticles by conjugating various specific ligands has shown potential therapeutic efficacy in nanomedicine. However, poor penetration of antitumor drugs into solid tumors remains a major obstacle. Here, we describe a targeting strategy for antitumor drug delivery by conjugating a crosslinked multilamellar liposomal vesicle (cMLV) formulation with a tumor-penetrating peptide, iRGD. The results showed that iRGD peptides could facilitate the binding and cellular uptake of drug-loaded cMLVs and consequently enhance the antitumor efficacy in breast tumor cells, including multidrug-resistant cells. Moreover, colocalization data revealed that iRGD-conjugated cMLVs (iRGD-cMLVs) entered cells via the clathrin-mediated pathway, followed by endosome-lysosome transport for efficient drug delivery. Finally, in vivo study indicated that iRGD-cMLVs could deliver anticancer drugs efficiently to mediate significant tumor suppression.